First readers of Shakespeare's sonnets, 1590-1790 - Acker, Faith D. (New York, NY : Routledge, 2021)
For more than four centuries, cultural preferences, literary values, critical contexts, and personal tastes have governed readers' responses to Shakespeare's sonnets. Early private readers often considered these poems in light of the religious, political, and humanist values by which they lived. Other seventeenth- and eighteenth- century readers, such as stationers and editors, balanced their personal literary preferences against the imagined or actual interests of the literate public to whom they marketed carefully curated editions of the sonnets, often successfully. Whether public or private, however, many disparate sonnet interpretations from the sonnets' first two centuries in print have been overlooked by modern sonnet scholarship, with its emphasis on narrative and amorous readings of the 1609 sequence. First Readers of Shakespeare's Sonnets reintroduces many early readings of Shakespeare's sonnets, arguing that studying the priorities and interpretations of these previous readers expands the modern critical applications of these poems, thereby affording them numerous future applications. This volume draws upon book history, manuscript studies, and editorial theory to recover four lost critical approaches to the sonnets, highlighting early readers' interests in Shakespeare's classical adaptations, political applicability, religious themes, and rhetorical skill during the seventeenth and eighteenth centuries
The passionate pilgrim and Shakespeare's 'sugred' reputation -- Reading and revising Shake-Speare's sonnets (1609) -- The manuscripts of Sonnet 2: sex, sonnets, and spirituality -- John Benson's sonnet sequences (poems: written by Wil. Shake-Speare. Gent.) -- Celebrations of church and king: an early Cambridge reader -- Restoration revisions: musical, dramatic, and miscellany readings -- Supplementing Shakespeare and creating the canon -- Edmond Malone: plotting the sonnets -- Reading the sonnets after Malone: independent responses
OCLC-licensed vendor bibliographic record.
Keywords: Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616 -- Criticism and interpretation -- History